The Role of Advanced Endoscopic Resection of Diverse Skull Base Malignancies: Technological Analysis during an 8-Year Single Institutional Experience - Rutland, John W.; Goldrich, David; Loewenstern, Joshua; Banihashemi, Amir; Shuman, William; Sharma, Sonam; Balchandani, Priti; Bederson, Joshua B.; Iloreta, Alfred M.; Shrivastava, Raj K. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Resection of skull base malignancies poses complex pathological and treatment-related morbidities. Recent technological advancements of endoscopic endonasal surgery (EES) offer the ability to reexamine traditional treatment paradigms with endoscopic procedures. The utility of EES was quantitatively examined in a longitudinal series with attention to morbidities and postoperative outcomes.Methods A single-center retrospective review was performed of all malignant sinonasal tumors from 2010 to 2018. Patients with purely EES were selected for analysis. Disease features, resection extent, complications, adjuvant treatment, recurrence, and survivability were assessed. Despite the mixed pathological cohort, analysis was performed to identify technical aspects of resection.Results A total of 68 patients (47.6% males and 52.4% females, average age: 60.3 years) were included. A diversity of histotypes included clival chordoma (22.1%), olfactory neuroblastoma (14.7%), squamous cell carcinoma (11.8%), and adenoid cystic carcinoma (11.8%). Gross total resection (GTR) was achieved in 83.8% of cases. Infection (4.4%) and cerebrospinal fluid leak (1.5%) were the most common postoperative complications. Total 46 patients (67.6%) underwent adjuvant treatment. The average time between surgery and initiation of adjunctive surgery was 55.7 days.Conclusion In our 8-year experience, we found that entirely endoscopic resection of mixed pathology of malignant skull base tumors is oncologically feasible and can be accomplished with high GTR rates. There may be a role for EES to reduce operative morbidity and attenuate time in between surgery and adjuvant treatment, which can be augmented through recent mixed reality platforms. Future studies are required to systematically compare the outcomes with those of open surgical approaches.
Keywords: endoscopic endonasal surgery; skull base malignancy; craniofacial resection; gross total resection; oncological outcomes